Masculinity discourse on media text: A critical review about news about violence on online news portals - Daniel Susilo (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Media as a medium plays a significant role in strengthening gender concept in society. Female’s sexualities are viewed as an object of judgement for the media. For the sake of men readers’ satisfaction, media justifies itself in its attempts to exploit women sexuality. Masculine’s way of thinking has been perpetuated in reports about women. Masculine men are considered empowering female’s bodies. Violence acts are considered as the form of masculine domination over feminine beings. This research aims to dismantle how media construct their texts on masculine discourses on online news portals. Online news portals are required to be swift in uploading news and using their acquired resources; thus, they perpetuate this masculine discourse. Critical discourse analysis of Van Dick was employed to unravel masculine discourse structures on media texts at the largest news portals in Indonesia, Alexa.com; and Tribunnews.com; which belong to a corporate media, Kompas Gramedia. The findings of this research state that online news portals and their acquired resources strengthen violence labelling as a part of masculine domination over feminine beings.